Performance Evaluation of Sludge – Added Clay Bricks - Mohd Tajri, Muhammad Hafiz; HASHIM, NOR HASLINA (Progress in Engineering Application and Technology, 2025)
The papermaking industry produces a large amount of sludge through wastewater treatment processes, which has a significant impact on the environment if not managed properly. Conventional disposal methods such as landfilling and incineration are expensive and contribute to pollution and loss of valuable resources. Therefore, a sustainable approach is needed to manage this industrial waste. This study focuses on the potential reuse of paper industry sludge to produce clay bricks. The main objective of the study was to evaluate the suitability of sludge as an additive in bricks in terms of physical stability and environmental impact. The study included three main methods: characterization of sludge content in terms of moisture content and chemical composition, production of brick samples with 5%, 10%, 15%, and 20% sludge mixtures, and analysis of the mechanical performance and water absorption of the resulting bricks. The study showed that bricks with sludge content up to 15% met the MS 76:1972 standard regarding water absorption rate but not on compressive strength. SEM-EDX and additional colour tests also showed safe performance regarding structure and chemical effects. The sludge mixture helps reduce the weight of the bricks and improves their thermal insulation properties. In conclusion, the use of paper industry sludge in the production of clay bricks not only helps in sustainable industrial waste management but also has the potential to be an environmentally friendly alternative to traditional building materials. This study contributes to the development of green building materials and promotes a circular economy in the construction industry.